2014
DOI: 10.1080/13854046.2014.958536
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Side-effects of Electroconvulsive Therapy in Elderly Depressed Patients

Abstract: Knowledge about cognitive side-effects induced by electroconvulsive therapy (ECT) in depressed elderly patients is sparse. In this study we investigated changes in the cognitive functioning of non-demented elderly depressed patients receiving ECT (n = 62) compared with healthy elderly people (n = 17). Neuropsychological tests were administered at the start of treatment and again within 1 week after treatment. We computed reliable change indices (RCIs) using simple regression methods. RCIs are statistical metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 68 publications
0
21
0
2
Order By: Relevance
“…Compared with pharmacotherapy, ECT is administered to a higher proportion of elderly patients relative to younger adults (Sackeim, 2005). ECT can cause acute cognitive side effects, including postictal confusion, impaired storing of new memories (anterograde amnesia) and lost memory for information that was gained before ECT (retrograde amnesia) (Dybedal, Tanum, Sundet, Gaarden, & Bjølseth, 2014;Kellner et al, 2010;Kessler et al, 2014). A meta-analysis indicated that anterograde amnesia typically resolves in adult patients within 15 days after ECT (Semkovska & McLoughlin, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Compared with pharmacotherapy, ECT is administered to a higher proportion of elderly patients relative to younger adults (Sackeim, 2005). ECT can cause acute cognitive side effects, including postictal confusion, impaired storing of new memories (anterograde amnesia) and lost memory for information that was gained before ECT (retrograde amnesia) (Dybedal, Tanum, Sundet, Gaarden, & Bjølseth, 2014;Kellner et al, 2010;Kessler et al, 2014). A meta-analysis indicated that anterograde amnesia typically resolves in adult patients within 15 days after ECT (Semkovska & McLoughlin, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…The test-retest reliabilities of measures of retrograde amnesia are expected to be high in healthy controls. 40 In a previous study, 36 we report very high test-retest correlations from T1 to T2 on the MQ (Spearman's correlation coefficient of 0.96) in our control group consisting of healthy elderly people (n = 17). Seven (11%) of 61 patients lost more points on the MQ from T1 to T2 than any of the healthy controls.…”
Section: Neurocognitive Assessmentmentioning
confidence: 83%
“…36 A psychologist and a trained test assistant conducted the measurements of cognitive functions. General cognitive ability was assessed at the baseline with the Vocabulary subtest from the Wechsler Abbreviated Scale of Intelligence.…”
Section: Neurocognitive Assessmentmentioning
confidence: 99%
“…Systematic reviews identify autobiographical memory (AM) difficulties as the ECT side-effect that is of most concern to patients (Dybedal et al, 2014;Fraser et al, 2008;Goodman, 2011;Rose et al, 2003). These reviews also agree that, due to the complexity of AM function, reliably measuring its loss following treatment represents a methodological challenge.…”
Section: Introductionmentioning
confidence: 99%